Principles for Placement of Traffic Intersections at Different Levels (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Essentially, in this stage we are talking about creating good conditions at the intersections of small towns and roads, for example: high-speed roads, main streets, streets and roads of local importance, residential streets, industrial and warehouse streets, passages for transport connections of regional importance, etc. d.